Mapping the corneal thickness and volume in patients with Down syndrome: a comparative population-based study - Hassan Hashemi (Arquivos Brasileiros de Oftalmologia)
ABSTRACT Purpose: To measure the central-to-peripheral corneal thickness and its volume according to age and gender in 10-30-year-old patients with Down syndrome (DS) and in matched individuals without DS. Methods: In the report, 202 normal pattern right eyes of patients with Down syndrome and 190 right eyes of individuals without Down syndrome and compared averages using independent sample t-tests and multiple linear regression models. The measured variables included the apical corneal thickness; the minimum corneal thickness; the average thickness on rings at 2 mm (R2), 3 mm (R3), and 4 mm (R4); the corneal volume in the central zones at 2-, 3-, 4-, and 10-mm diameters; Ambrosio’s relational thickness; and the pachymetric progression indices. Results: The mean age of the participants was 16.99 ± 4.70 and 17.22 ± 4.54 years (p=0.636). The means ± SD were 516.7 ± 33.0 and 555.7 ± 33.1 µm for apical corneal thicknesses, 508.0 ± 33.5 and 549.0 ± 40.6 µm for minimum corneal thicknesses, 543.0 ± and 588.4 ± 33.8 µm for R2s, 584.9 ± 35.6 and 637.0 ± µm for R3s, 646.9 ± 38.5 and 707.6 ± 37.1 µm for R4s, 396.4 ± 102.3 and 462.7 ± 96.2 µm for Ambrosio’s relational thicknesses, 1.36 ± 0.37 and 1.22 ± 0.18 for pachymetric progression index maximums, 1.62 ± 0.11 and 1.74 ± 0.11 mm3 for corneal volume at 2 mm, 3.73 ± 0.24 and 4.01 ± 0.24 mm3 for corneal volume at 3 mm, 6.76 ± 0.44 and 7.30 ± 0.43 mm3 for corneal volume at 4 mm, and 57.03 ± 3.44 and 61.51 ± 3.40 mm3 for total corneal volume in the Down syndrome and control groups, respectively (all p<0.001). All the above indices were inversely related to age, but not to gender. Ambrosio’s relational thickness maximum and the pachymetric progression index maximum were independent of age and gender. Conclusion: Non-keratoconic patients with Down syndrome had thin corneas with a homogeneous distribution. Therefore, the reference ranges of cornea thickness and volume should be re-defined for this patient population.